PENERAPAN METODE MONTESSORI DALAM MENGEMBANGKAN CALISTUNG SISWA DI KELAS 1 SDN KADUDAMPIT - Raida Namira Aulia; Andi Fatimah Husayma; Andromeda Valentino Sinaga (STKIP Subang, 2023)
The study aims to answer questions: 1) how to apply the montessori method to teachers to apply it to first - grade students in the kadudampit state school; 2) how could calistung 1 - year students in the country's sd be bdampit in KBM (teaching learning activities) before using the montessori method; 3) how could calistung 1 student in the country's kadudampit be capable after using the montessori method; 4) there is a significant difference between calistung 1b students' ability in experiment class before and after using the montessori method and a control class that does not use the montessori method. The method used in this study is pseudo experiments. Instruments used in this research data collection include interviews, observations, and class action research (PTK). The samples taken in this study are 1b students as an experimental class and 1a as a control class. Calistung students' performance on KBM before being fully operational would be minimal. And students' abilities in calistung development in the appeal classes have been increased. Thus there is a significant difference between students' ability to speak in the development of the calistung in the experimentation class and the control class. The results of this study were reinforced based on the results of post-test done by offering a reflection of learning. The study concludes that the ability of calistung students in the 1b primary school of the cadudampit who had conducted experiments increased significantly and differentiated after being treated by the montessori methods. Lower-class teachers, especially teachers in first class can use the montessori method as an alternative to the method used on KBM implementation to improve calistung students' capabilities and should be conducted advanced studies of the montessori method in other learning to prove the effectiveness of the montessori method that is applied to other learning.